The Grammatical Error Analysis in English Conversation of the Eleventh-Grade Students of Senior High School Level - Chamelya Vivi Crystanty Sene (Departement of Mathematics Education, 2023)
The following questions are the focus of this research article: What kinds of grammatical errors do students in the eleventh grade make in their conversations? And which kind of grammar error do eleventh graders make the most frequently in their conversations? To answer those questions, the writer used a descriptive method. The subjects of this study were eleventh grade students. In collecting the data, the writer used conversation, and the topics were “meeting a new friend,